Assessment of Maternal Mortality in Federal Medical Centre Jalingo Using ARIMA Model - Mathias, Felix Melang; Joshua, ThankGod; Bamigbala, Olateju Alao; Sayuti, Fatima Yahaya (Darul Yasin Al Sys, 2025)
Nigeria bears a disproportionate burden of global maternal mortality, contributing approximately 10% of all maternal deaths worldwide. This study adopts a multi-theoretical and empirical approach to analyze the complex interplay of socio-cultural, economic, and systemic determinants influencing maternal mortality in Nigeria. Grounded in models such as the Three Delays Model, Health Belief Model, Social Determinants of Health, Andersen’s Behavioral Model, and the Cultural and Structural Competency Framework, the research highlights the multifaceted barriers impeding timely and effective maternal care. Empirical findings based on Autoregressive Integrated Moving Average (ARIMA) modeling reveal persistent, though insufficient, declines in maternal and child mortality over recent decades. Additionally, socioeconomic variables such as low levels of female education, high fertility rates, poverty, and inadequate access to antenatal care significantly correlate with maternal mortality rates. The study critiques existing interventions as poorly coordinated and unsustainable, with limited community involvement and cultural adaptation. Recommendations emphasize a multilevel prevention strategy—ranging from primordial to quaternary levels—integrating structural reforms, community-based education, capacity-building among healthcare providers, and a reconfiguration of national health policy. The findings contribute to the growing body of knowledge on maternal health by providing a comprehensive, culturally-informed, and data-driven analysis aimed at guiding future research, policy, and practice.